Sørpe full, sveiseblind og stinn som et eggebrød - Hylland, Ole Marius (Tidsskrift for kulturforskning, 2021)
This article discusses possible analytical perspectives on oral language - the vernacular, the slang, the spoken language - in cultural history and folkloristics. The starting point for the article is an attempt to investigate how many words in the Norwegian language are used to describe the state of being drunk. Intoxication is an area where linguistic creativity is great. In this article, a potential analysis of this creativity is exemplified through a systematic review of eight different categories of synonyms for drunk. The article shows furthermore how the empirical interest in vernacular language has shifted between different academic disciplines, and I argue that what we might call popular conceptual history clearly belongs within the discipline of cultural history/folkloristics.